Diel patterns of fin whale 20 Hz acoustic presence in Eastern Antarctic waters. Issue 4 (19th April 2023) - Aulich, Meghan G.; Miller, Brian S.; Samaran, Flore; McCauley, Robert D.; Saunders, Benjamin J.; Erbe, Christine
Abstract : This study presents evidence of diel patterns in fin whale ( Balaenoptera physalus ) 20 Hz acoustic presence in Eastern Antarctic waters. Passive acoustic recordings were collected at four sites in Eastern Antarctica from 2013 to 2019. A generalized linear model fitted by a generalized estimating equation was used to test the hypothesis that fin whale 20 Hz acoustic presence shows significant variation between light regimes dawn, day, dusk and night. In the Indian sector of Antarctica, at the Prydz and Southern Kerguelen Plateau sites, fin whale acoustic presence was significantly more common during the night and dawn before declining during the day and dusk periods. A different diel pattern was observed in the Pacific sector, at the Dumont d'Urville site: fin whale acoustic presence was significantly more common during the day than dusk and night periods. No diel pattern was identified at the Casey site. The identified diel patterns in the Indian sector of Eastern Antarctica correlate with previously identified diel patterns of the fin whales' prey. We suggest an indirect association between fin whale acoustic presence and foraging, with the animals more likely to produce the 20 Hz pulse during the night when not foraging and less likely to vocalize when foraging during the day.